2011
DOI: 10.1515/cclm.2011.075
|View full text |Cite
|
Sign up to set email alerts
|

The ROMA (Risk of Ovarian Malignancy Algorithm) for estimating the risk of epithelial ovarian cancer in women presenting with pelvic mass: is it really useful?

Abstract: The ROMA is a simple scoring system which shows excellent diagnostic performance for the detection of EOC in post-menopausal women, but not in pre-menopausal women. Moreover, the dual marker combination of HE4 and CA125 (ROMA) does not show better performance than HE4 alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
113
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 27 publications
21
113
2
2
Order By: Relevance
“…They suggested that ROMA was less specific but more sensitive than HE4, while both ROMA and HE4 were more specific than CA125 for EOC prediction. On contrary, a previous report (Montagnana et al, 2011) has demonstrated that ROMA did not show better diagnostic performance than HE4 alone in the diagnosis of ovarian cancer. Additionally, in another study (Van Gorp et al, 2011), it has been reported that combining HE4 and CA125 in the ROMA improved HE4 but not CA125 performance, indicating that ROMA and HE4 did not perform significantly better than CA125 alone.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…They suggested that ROMA was less specific but more sensitive than HE4, while both ROMA and HE4 were more specific than CA125 for EOC prediction. On contrary, a previous report (Montagnana et al, 2011) has demonstrated that ROMA did not show better diagnostic performance than HE4 alone in the diagnosis of ovarian cancer. Additionally, in another study (Van Gorp et al, 2011), it has been reported that combining HE4 and CA125 in the ROMA improved HE4 but not CA125 performance, indicating that ROMA and HE4 did not perform significantly better than CA125 alone.…”
Section: Discussionmentioning
confidence: 58%
“…There may be several explanations for the heterogeneity observed among previous studies, and in our opinion, the most intriguing are the differences in the study design, study population, demographic characteristics of patients, ovarian cancer prevalence, sample size, control group (healthy women or women with benign diseases), methods of measuring serum CA125 or HE4 levels (ELISA or chemiluminescent microparticle immunoassay) and cutoff values of CA125/HE4 assays (manufacturer or clinical practice). Furthermore, several studies did not take into account the effect of the uneven distribution of patients in pre-and post-menopausal status, histological subtypes and FIGO stages when interpreting the results of CA125 and HE4 measurements (Moore et al, 2009;Moore et al, 2010;Kim et al, 2011;Montagnana et al, 2011;Ruggeri et al, 2011;Van Gorp et al, 2011). Overall, each of these points theoretically represent a source of heterogeneity among studies likely influencing the markers' diagnostic performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This and other studies have shown that ROMA is able to deliver an improved accuracy over either mark alone. Montagnana et al reported that preoperative ROMA calculation performed better than CA125, but no advantage could be found when compared to HE4 alone [12]. The application of HE4 for the prognosis and prediction of relapse for ovarian cancer patients has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Nassir et al reported that HE4 in combination with CA125 performed better than CA125 and HE4 alone in predicting relapse within 12 months after first-line chemotherapy [17]. Overall, HE4 has been demonstrated to be a more efficient marker for ovarian cancer than CA125, and it can be used either alone or as a part of ROMA in the differential diagnosis of pelvic masses and prediction of relapse for ovarian cancer patients after treatment [10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%